2013
DOI: 10.3390/rs5062660
|View full text |Cite
|
Sign up to set email alerts
|

Using Satellite Data to Represent Tropical Instability Waves (TIWs)-Induced Wind for Ocean Modeling: A Negative Feedback onto TIW Activity in the Pacific

Abstract: Recent satellite data and modeling studies indicate a pronounced role Tropical Instability Waves (TIW)-induced wind feedback plays in the tropical Pacific climate system. Previously, remotely sensed data were used to derive a diagnostic model for TIW-induced wind stress perturbations (τ TIW ), which was embedded into an ocean general circulation model (OGCM) to take into account TIW-induced ocean-atmosphere coupling in the tropical Pacific. While the previous paper by Zhang (2013) is concerned with the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Coupled models are also used to examine the impacts of TIW on the tropical climate. It is demonstrated that TIW‐scale processes can have significant influences on large‐scale air‐sea interaction (An, ; Imada & Kimoto, ; Seo et al, ; Small et al, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Coupled models are also used to examine the impacts of TIW on the tropical climate. It is demonstrated that TIW‐scale processes can have significant influences on large‐scale air‐sea interaction (An, ; Imada & Kimoto, ; Seo et al, ; Small et al, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, α inter =1.3 and α TIW =3.0 were used for all HCM experiments discussed below. As seen in the OGCM simulations [ Zhang et al ., ], α TIW =3.0 can adequately represent TIW‐induced feedback strength in the eastern tropical Pacific when performing the HCM experiments.…”
Section: Model Descriptionsmentioning
confidence: 99%
“…These relationships are well captured in the HCM simulations. Following the previous analyses [e.g., Chelton , ; Zhang et al ., ], TIW activity in the ocean and TIW‐scale coupling were analyzed in terms of standard deviations of the SST TIW and τ TIW fields and the wind stress curl and divergence fields, respectively.…”
Section: The Effects Of Tiw Wind Forcing: a Feedback Run (Runfeedback)mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, several previous modeling studies have suggested a negative feedback induced by TIWs (Seo et al, 2007;Imada et al, 2012;Zhang et al, 2013). In a coupled ocean-atmosphere system, the atmospheric boundary layer (ABL) almost simultaneously responds to the presence of TIWs and as a feedback it returns its signal to the oceanic surface, which interacts in an opposite way with ocean surface fields (currents and temperature) that affect the oceanic dynamical and thermo-dynamical features (Polito et al, 2001;Pezzi et al, 2004;Seo et al, 2007).…”
Section: Introductionmentioning
confidence: 99%